Maximum Ride : the manga. 8 - Lee, NaRae; Patterson, James, 1947-; Patterson, James, 1947- (New York, NY : Yen Press, 2014)
To distance themselves from the debate over their future, Max and the Flock join a scientific expedition to the Antarctic, but the expedition is a trap for the super-human kids, set by an undeworld figure who has promised to deliver them to the highest bidder.
Based on: Maximum ride / James Patterson.
Young Adult.
Young Adult
Keywords: Patterson, James, -- 1947- -- Adaptations -- Juvenile literature; Patterson, James, -- 1947- -- Adaptations; Patterson, James, -- 1947- -- Adaptations; Genetic engineering -- Comic books, strips, etc -- Juvenile fiction; Good and evil -- Comic books, strips, etc -- Juvenile fiction; Scientists -- Comic books, strips, etc -- Juvenile fiction; Adventure and adventurers -- Fiction; Cartoons and comics; Genetic engineering -- Fiction; Good and evil -- Fiction; Science fiction; Scientists -- Fiction; Adventure graphic novels; Comic books, strips, etc; Genetic engineering -- Comic books, strips, etc -- Fiction; Good and evil -- Comic books, strips, etc -- Fiction; Graphic novels; Manga; Science fiction graphic novels; Scientists -- Comic books, strips, etc -- Fiction; Adventure fiction; Graphic novels; Science fiction comic books, strips, etc